Impact of defects on the electrical properties of BiFeO3 thin films - Reis, S. P. [UNESP]; Araujo, E. B. [UNESP] (Taylor & Francis Ltd, 2020)
The impact of defects on the electrical properties of bismuth ferrite thin films has been studied. Secondary phases and oxygen vacancies were the main defects considered. Thin films with secondary phases show higher conductivities than single-phase films. Monophasic films annealed in oxygen atmosphere shows lower conductivity than the non-annealed film. For selected thin film with secondary phase, the relaxation in the grain boundary was predominant with activation energy eV, suggesting the first ionization oxygen vacancies as the relaxation mechanism in the studied films. The electric field effect on relaxation processes was similarly to Arrhenius thermally activated process.
Keywords: Defects; bismuth ferrite; thin films